Effects of raw and poly(propylene oxide) grafted nanosilica on the morphology and thermal and mechanical properties of polyurethane foam. Issue 32 (14th May 2015) - Gao, Xia; Chen, Keping; Liang, Shuen; Fan, Chunchun; Huang, Yigang; Jia, Xiaorong; Tian, Chunrong; Wang, Jianhua
ABSTRACT Poly(propylene oxide) (PPO)‐grafted nanosilica (NS)/polyurethane foam (PUF) composites were synthesized by a ring‐opening polymerization catalytic process and reaction‐molding technology. The raw NS and PPO–NS were characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, and transmission electron microscopy. Scanning electron microscopy, dynamic mechanical analysis, and compressive strength tests were used to compare the morphology and thermal and mechanical properties of the PPO–NS/PUF and raw NS/PUF composites with a series of filler contents. The PPO–NS/PUF composites generally exhibited better morphology, thermal and mechanical properties than raw NS/PUF composites. Moreover, the PPO–NS/PUF composites with lower contents (0.5, 1 php) of filler showed even higher mechanical reinforcement than that with higher contents (1.5, 2 php) of filler, which was caused by the interaction between additives and PUF matrix. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42400.